2015
DOI: 10.1371/journal.pone.0125912
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profile in Bovine Granulosa Cells of Preovulatory Dominant and Subordinate Follicles during the Late Follicular Phase of the Estrous Cycle

Abstract: In bovine, ovarian follicles grow in a wave-like fashion with commonly 2 or 3 follicular waves emerging per estrous cycle. The dominant follicle of the follicular wave which coincides with the LH-surge becomes ovulatory, leaving the subordinate follicles to undergo atresia. These physiological processes are controlled by timely and spatially expressed genes and gene products, which in turn are regulated by post-transcriptional regulators. MicroRNAs, a class of short non-coding RNA molecules, are one of the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 56 publications
3
80
1
Order By: Relevance
“…Other identified differentially expressed miRNAs that exhibited increased expression levels in COCs in this study, such as miR‐342 and miR‐542‐5p , were recently identified in EVs from bovine FF and found to be more highly expressed in large than in small follicles (Navakanitworakul et al., ). Similarly, let‐7a‐3p and miR‐542‐5p, whose expression was found to be increased in COCs compared to in GCs in this study, were previously determined to be down‐ and upregulated, respectively, in granulosa cells from bovine pre‐ovulatory compared to in subordinated follicles (Gebremedhn et al., ). Together, these results suggest that let‐7a‐3p and miR‐542‐5p likely play a different role in COCs, which is independent of the follicle stage.…”
Section: Discussionsupporting
confidence: 74%
“…Other identified differentially expressed miRNAs that exhibited increased expression levels in COCs in this study, such as miR‐342 and miR‐542‐5p , were recently identified in EVs from bovine FF and found to be more highly expressed in large than in small follicles (Navakanitworakul et al., ). Similarly, let‐7a‐3p and miR‐542‐5p, whose expression was found to be increased in COCs compared to in GCs in this study, were previously determined to be down‐ and upregulated, respectively, in granulosa cells from bovine pre‐ovulatory compared to in subordinated follicles (Gebremedhn et al., ). Together, these results suggest that let‐7a‐3p and miR‐542‐5p likely play a different role in COCs, which is independent of the follicle stage.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, looking into the miRNA expression patterns in follicles of different size (dominant and subordinate), healthy and atretic could be a step forward towards identification of miRNAs that are potentially involved in follicular development and ovulation. With this respect, previous studies have shown differential expression of miRNAs that are involved follicular cell proliferation, steroidogenesis, luteinization, and oocyte maturation between small and large follicles or between healthy and atretic bovine follicles [31][32][33]. Moreover, miRNAs that are potentially involved in Wnt signalling pathway, Transforming growth factor (TGF-beta) signalling pathway, axon guidance and apoptosis were differential expressed between small and bigger follicles at day 3 of the bovine oestrous cycle ( Figure 1) while miRNAs that were involved in metabolism of vitamins, cofactors, lipids, lipoproteins, cysteine and methionine were differentially expressed between small and bigger follicles at day 7 of the estrous cycle [31].…”
Section: The Role Of Cellular Mirnas In Follicular Development and Oomentioning
confidence: 99%
“…Apart from this, understanding miRNA expression patterns during the follicular phase of the estrous cycle would provide a better clue about miRNAs that directly involved in ovulation. With this regard, our previous study have shown miRNAs that potentially involve in cell adhesion, cell proliferation, apoptosis and metabolism were significantly different between the granulosa cells of preovulatory dominant and subordinate follicles at day 19 of the bovine oestrous cycle [32]. Similarly, in zebra fish it is believed that small early vitellogenic follicles are unable to undergo oocyte maturation whereas oocytes in mid-to late vitellogenic follicles can be induced by Luteinizing hormone (LH) to become matured.…”
Section: The Role Of Cellular Mirnas In Follicular Development and Oomentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that these miRNAs might regulate the phenotypic characters of different cell types by controlling the expression of important signalling molecules (Donadeu et al, ). Additionally, miR‐708, miR‐221, miR‐21‐3p, miR‐335, and miR‐214 are expressed abundantly in the follicular fluid of SFs compared to that of DFs (Gebremedhn et al, ) indicating a potential role in the selection of follicles. Hence, differential expression of miRNAs between TCs and GCs may play an important role in the selection and recruitment of DFs, as well as during the follicular wave (in different mammalian species the recruitment, growth and development of several waves of follicles is possible before follicle rupture and ovulation occur; during this process two or more follicles might develop, but only one follicle successfully releases the egg) and atresia.…”
Section: Roles Of Mirnas In Female Reproductionmentioning
confidence: 99%